Case Report: Clinical Analysis of Seven Neonates With Prader-Willi Syndrome and Review of the Literature - Hu, Yu; Xue, XinDong; Fu, JianHua (Frontiers in Pediatrics, 2021)
Objective: The clinical symptoms of neonatal Prader-Willi syndrome (PWS) are not typical and are easy to miss. The aim of the study was to investigate the clinical features and genetic characteristics of seven cases of neonatal PWS from northern China, and to improve the understanding of PWS in neonates. Methods: We retrospectively analyzed seven infants diagnosed by methylation specific multiplex ligation probe amplification technology (MS-MLPA) in the Neonatology Unit of Shengjing Hospital of China Medical University from September 2016 to July 2020. Results: All seven cases involved full term or nearly full-term infants born to mothers without a history of abnormal pregnancy or delivery. Difficulty in feeding occurred immediately after birth in infants with decreased hypotonia. Five patients had characteristic craniofacial morphology, such as a prominent forehead, narrow face, almond-shaped eyes, small mouth, and downturned mouth. Further, three of the seven infants had patent ductus arteriosus (PDA). In addition, three neonates had hyperammonemia, hypoglycemia, and idiopathic edema, respectively. PWS could be effectively diagnosed and genotyped by MS-MLPA. Conclusion: Neonates with PWS have hypotonia and feeding difficulty. Characteristic facial features and genital hypoplasia are common in neonatal PWS. Infants with PWS may be predisposed to PDA, hypoglycemia, hyperammonemia, and edema.